Rural Nurses' Perceptions of Disruptive Behavior and Clinical Outcomes: A Pilot Study - Kara Addison; Susan Luparell (Rural Nurse Organization; Binghamton University, 2014)
Purpose: The purpose of this pilot study was to explore rural nurses' perceptions regarding disruptive behavior and its impacts on interdisciplinary relationships, patient safety, and patient outcomes. Methods: Montana nurses working at either of two rural facilities, one a small hospital and the other a critical access facility, participated in the study. The study replicated a larger study conducted by Rosenstein and O'Daniel (2005) in the VHA West Coast hospital network. A questionnaire was sent to nurses electronically via their agency's email system to assess perceptions of disruptive behavior and its effects on patient outcomes. Findings: Fifty-seven nurses participated in the study, yielding a 47.5% response rate. Disruptive behavior was reported to be displayed more often by nurses than physicians in this study. Nurses perceived that disruptive behavior is linked to adverse events, and may also have a negative impact on patient safety and satisfaction. In addition, participants perceived a link between disruptive behavior and the psychological and behavioral variables impacting individual nurses. Finally, the majority of respondents indicated that their facility lacked appropriate reporting and counseling policies for addressing disruptive behavior. Conclusions: Like their VHA West Coast counterparts, nurses working in rural settings experience disruptive behavior and believe there is a link between disruptive behavior and negative patient outcomes. However, results from this pilot study suggest that disruptive behavior by nurses in rural settings is more prevalent than that of physicians, findings that contradict previous work. DOI:  http://dx.doi.org/10.14574/ojrnhc.v14i1.300  Key words: Disruptive behavior, workplace incivility, patient outcomes, patient safety, rural nursing